Emerging trends in gene-modified-based chimeric antigen receptor–engineered T-cellular therapy for malignant tumors: The lesson from leukemia to pediatric brain tumors. Issue 8 (29th May 2020) - Lin, Wen-Ying; Chen, Yi-Wei; Lin, Chun-Fu; Yang, Yi-Ping; Wang, Mong-Lien; Hung, Kai-Feng; Huang, Pin-I; Lee, Yi-Yen; Chiou, Shih-Hwa
Abstract : In 2017 and 2018, Food and Drug Administration has approved YESCARTA (axicabtagene ciloleucel) and KYMRIAH (tisagenlecleucel), two chimeric antigen receptor (CAR)-engineered T-cell products, for B-cell malignancies. It also marked a watershed moment in the development of immunotherapies for cancer. Despite the successes in adults, it remains clinically applicable only in B-cell acute lymphoblastic leukemia in pediatrics. Notably, multiple clinical trials and recent case reports about childhood central nervous system (CNS) tumors, the leading cause of deaths in children, have emerged and granted promising results. With the growing consideration of the biological responses in the interaction of human immunity, the major technical obstacles such as on-target off-tumor toxicity in widespread solid tumors, antigenic heterogeneity, adaptive resistance, difficult T-cell (CD4/CD8) trafficking, and immunosuppressive environments in CNS are gradually approached and ameliorated. The new spotlights of this review are focusing on current development, and emerging treatments for pediatric CNS tumors integrating molecular research with the mainstream of CAR-T therapeutic strategies to sketch a main axis and pathway forward in the improvement of novel gene-modified–based cellular platform.